Haemorrhagic risk of oncology patients with myocardial infarction. (25th November 2020) - Branco Mano, T; Timoteo, A.T; Aguiar Rosa, S; Cruz Ferreira, R
Abstract:  : The approach of acute coronary syndrome (ACS) in oncology patients (pts) is challenging due to higher haemorrhagic risk. Objectives and methods: Retrospective analysis of pts included in an ACS registry between October 2010 and September 2019 with cancer (active or diagnosed in <5 years). Aim: evaluate safety and efficacy of single vs dual antiplatelet therapy (DAPT), anticoagulation and revascularization strategy. Primary safety endpoint: major haemorrhagic events (MHE). Secondary efficacy endpoints: ischemic events, intra-hospital (IH) mortality; combined efficacy endpoint of IH mortality, reinfarction and ischemic stroke. Results: 934 pts (5%) of a total of 18845 pts with ACS had diagnosis of cancer. Compare to pts without malignancy, oncology pts were older, had more atrial fibrillation (AF), lower left ventricle ejection fraction (LVEF), underwent invasive coronary angiography (ICA) and angioplasty less often. Oncology pts had more events: MHE (2.9% vs 1.5%, p<0.001), mortality (5.8% vs 3.4%, p<0.001) and combined endpoint (7.4% vs 4.9%, p<0.001). Oncology population: pts with MHE (N=27) had more previous haemorrhagic events, AF, higher creatinine level, ST-Elevation Myocardial Infarction (STEMI), more use of anticoagulation, less use of DAPT or acetylsalicylic acid (ASA) and higher IHmortality. In multivariate analysis, previous haemorrhagic events, AF, STEMI and no ASA were independent predictors of MHE. Pts who reached combined endpoint (N=69) were older, had more renal impairment, thrombocytopenia, STEMI, Killip class > I, lower LVEF, less prescribe with antiplatelet therapy and neurohormonal therapy, less submitted to ICA and a trend to less angioplasty. In multivariate analysis, STEMI, Killip >I, creatinine >2mg/dL, thrombocytopenia, LVEF<40%, no ACEi therapy and no ICA were independent predictors of the combined endpoint (Table 1). Conclusion: Oncology pts had worse prognosis than general population with ACS. MHE were mainly related to previous haemorrhagic event and AF, associated with anticoagulation strategy. On the other hand, IH mortality, reinfarction and ischaemic stroke were associated with lower use of antiplatelet and neurohormonal therapy and ICA. Funding Acknowledgement: Type of funding source: None